A short proof of the Cushing-Henson conjecture - Stevo Stevic (Discrete Dynamics in Nature and Society)
We give a short proof of the Cushing-Henson conjecture concerning Beverton-Holt difference equation, which is important in theoretical ecology. The main result shows that a periodic environment is always deleterious for populations modeled by the Beverton-Holt difference equation.